Analisis Implementasi Kurikulum Merdeka pada Tahap Perencanaan, Pelaksanaan, dan Evaluasi di SMA Negeri 1 Pamboang Majene: Penelitian - Sufyan Hakim; Nur Amaliah; Surahmi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
An independent curriculum is a curriculum that gives schools, teachers and students the freedom to learn independently, be creative and innovate. The aim of this research is to find out how the independent curriculum is implemented at SMA Negeri 1 Pamboang starting from the planning, implementation and evaluation stages. This research use descriptive qualitative approach. The instrumens used in this research are questionnaires, interviews and observations. The data analysis tehnique used consists of 4 steps, namalydata collection, data reduction, data display and verification. The results of this research show that the implementation of the independent curriculum in driving schools consists of 3 stages starting from the planning stage which consists of creating teaching modules, assessment instruments and the P5 module (Strengthening Pancasila Student Profile Project). After that, the implementation phase starts wict intracurricular learning by implementing differentiated learning (differentiation of content, processes and products). The final stage is the assessment or evaluation stage which consists of 3 assessments, namely diagnostic assessment (cognitive and non-cognitive), formative assessment and summative assessment. Based on the analysis of the implementation of the independent curriculum at SMA Negeri 1 Pamboang, severa obstacles were found. These obstacles have of course received solutions from the principal, deputy principal, and teachers of SMA Negeri 1 Pamboang.